NILAI BIOLOGIS PROTEIN PADA DOMBA LOKAL JANTAN YANG DIBERI PAKAN MENGANDUNG KONSENTRAT DAN JERAMI PADI YANG DIFERMENTASIKAN MENGGUNAKAN UREA DAN URIN - Wahyu Subagio Saputro; Endang Purbowati; Edy Rianto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2016)
This study aims to carry out the effects and measure the amount of biological value of dietary protein in local rams which were fed concentrate (2.3% body weight) and rice straw ad libithum. Twelve local rams, aged about 1 year old and weighed 25.44 kg ± 1.60 (CV = 6.12), were allocated to three type of feeding treatments. The treatments applied were rice straw without treatment (T0), rice straw treated with urea (T1), and rice strawtreated with urine (T2). The parameters observed were dry matter (DM) intake, crude protein (CP) intake, CP digestibility, CP metabolisability and biological value of dietary protein. The data then was analysed using ANOVA and the results showed no difference at all parameters which observed. Average of DM intake was 895.86 g/d, CP intake was 152.24 g/d, CP digestibility was 77.34%, CP metabolisability was 65.66% and biological value of dietary protein was 84.88%. The conclusion of this research was the rice straw which had treatment with urea or urine did not affect in biological value of dietary protein.